The role of search engine optimization, content marketing and influencer marketing in somenthinc purchasing decision making - Dwiyanti, Ade Thessa; Nafila, Nida; Rahmadi, Rahmadi (Institute of Computer Science (IOCS), 2025)
The skincare industry is experiencing rapid growth with intense competition and shifts in online shopping behavior. This study aims to examine the role of search engine optimization, content marketing, and influencer marketing on purchasing decisions. This research seeks to provide insight into marketing effectiveness in the digital age. By using causal associative quantitative methods to analyze the relationship between variables. Primary data was collected through questionnaires from 150 respondents, namely consumers or potential consumers of Somethinc products in Cirebon. Sampling was done by purposive sampling technique. Data analysis using SEM PLS with SmartPLS 3.0 software. The results showed that influencer marketing has the most influence on purchasing decisions for Somethinc products in Cirebon, followed by content marketing, while SEO has the least influence. SEO can ensure products are easy to find, Content Marketing creates a good impression, and Influencer Marketing provides a strong impetus for customers to make purchasing decisions